Stress, self-esteem, coping skill and treatment strategies among victim of earthquake at Kampung Mesilau Ranau, Sabah - Wan Othman, Wan Norhayati; Zainudin, Zaida Nor; Yahya, Siti Aishah; Omar, Mohamad Nazli; Mamat, Suzyliana (Human Resource Management Academic Research Society, 2019)
The purpose of this study was to investigate the level of stress, self-esteem and coping skill of the victims of earthquake at Kampung Mesilau, Ranau Sabah. Besides that, this study also investigate the relationship between stress, self-esteem and coping skill. The study was conducted on 210 respondents from the village of Mesilau, Ranau Sabah. The instrument used is Depression Anxiety Stress Scale (DASS) to measure stress, Rosenberg Self Esteem to measure self-esteem and the COPE Scale (COPE) to measure the coping skill among the respondents. The results showed that the level of stress was mostly in the normal level of 125 people (72.94%), the level of self-esteem was mostly in the low level of 125 people (59.6%) and the level of coping skill mostly was good, 107 (51.0%). The results also found that there was no relationship between stress and self-esteem with coping skill, r =.162, p>.05 and r = .162, p >.05. Through the findings of this study, it can provide an input to the local community and community leaders to prepare for the eventual earthquakes in the future.